Highly tunable refractive index visible-light metasurface from block copolymer self-assembly - Ju Young Kim (Nature Portfolio, 2016)
Wider control of the refractive index is desired for new optical applications. Here the authors manipulate block copolymer self-assembled nanopatterns via shrinkage in order to control the refractive index. They achieve an index above 3 over 1,000 nm bandwidth.